Դիտարկումներ Մակար Եկմալյանի և Կոմիտասի դաշնակած պատարագի մոնոդիաների մեղեդիական մտածողության շուրջ - Արևշատյան, Աննա (Մատենադարան)
In the last quarter of the 19th century, several experiments of polyphonic revision of the Liturgy of the Armenian Apostolic Church were carried out, among which the highly artistic versions of Makar Yekmalyan and Komitas are in the first place. The article examines the melodies of the liturgic chants The Deep Sacrament, Our Father and Holy, Holy, chosen by the founders of the national school of composers. The comparison showed that Komitas, on the whole, was inclined to choose a more archaic and less known monody, while Yekmalyan (as in the case of Our Father) preferred the melodic version characteristic of the era of Nersēs Shnorhali. One way or other, the singing tradition of the Armenian Church has preserved all these variants which are sung during the Liturgy to this day. В последней четверти XIX века было осуществлено несколько опытов полифонической обработки Литургии Армянской Апостольской церкви, среди которых первое место принадлежит высокохудожественным обработкам Макара Екмаляна и Комитаса. В статье рассматриваются варианты монодий песнопений «Глубокое Таинство», «Отче наш» и «Свят, Свят», избранные основоположниками национальной композиторской школы для многоголосных обработок Литургии. Сравнение показало, что Комитас в целом был склонен к выбору более архаичных и менее известных монодий, тогда как M. Екмалян предпочёл варианты, характерные скорее всего для эпохи Нерсеса Шнорали. Так или иначе, певческая традиция Армянской Церкви сохранила эти оба варианта. Они поются на Литургии и по сей день.
Keywords: Արվեստ; Հոգևոր երաժշտություն